1999
DOI: 10.1038/sj.bmt.1702069
|View full text |Cite
|
Sign up to set email alerts
|

Tissue plasminogen activator (tPA) as therapy for hepatotoxicity following bone marrow transplantation

Abstract: Summary:The treatment of established veno-occlusive disease (VOD) of the liver with tissue plasminogen activator (tPA) has been disappointing. In attempts to improve upon these results we identified a subgroup of patients with consistently elevated bilirubin levels who did not meet conventional criteria for VOD (Susp VOD) but who had a significant risk of later developing clinical VOD. In January 1994 we began to treat patients who developed Susp VOD with tPA rather than waiting until they developed clinical V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 10 publications
0
25
0
Order By: Relevance
“…Two clinical studies of moderate size assessing tPA and heparin treatment for VOD/SOS (n = 42 and n = 37) [38,39], and one trial of tPA with and without heparin (n = 56) [39] have reported response to tPA (resolution or improvement of VOD/ SOS symptoms) in approximately 23-52% of DRug EvaluatiOn Richardson, Grupp, Pagliuca, Krishnan, Ho & Corbacioglu future science group patients, although this was accompanied by significant bleeding in 24-35% [38][39][40]. The joint BCSH/BSBMT guideline does not recommend use of tPA for treatment of VOD/SOS due to the associated risk of bleeding [21]; guidelines from the European School of Haematology (ESH)-EBMT note that while tPA may be effective in some patients, it is contraindicated in those with MOF, hemorrhage or severe hypertension [33].…”
Section: Overview Of Vod/sos Therapiesmentioning
confidence: 99%
“…Two clinical studies of moderate size assessing tPA and heparin treatment for VOD/SOS (n = 42 and n = 37) [38,39], and one trial of tPA with and without heparin (n = 56) [39] have reported response to tPA (resolution or improvement of VOD/ SOS symptoms) in approximately 23-52% of DRug EvaluatiOn Richardson, Grupp, Pagliuca, Krishnan, Ho & Corbacioglu future science group patients, although this was accompanied by significant bleeding in 24-35% [38][39][40]. The joint BCSH/BSBMT guideline does not recommend use of tPA for treatment of VOD/SOS due to the associated risk of bleeding [21]; guidelines from the European School of Haematology (ESH)-EBMT note that while tPA may be effective in some patients, it is contraindicated in those with MOF, hemorrhage or severe hypertension [33].…”
Section: Overview Of Vod/sos Therapiesmentioning
confidence: 99%
“…The authors concluded that patients who met two McDonald criteria only had a better outcome as their liver damage was less severe and potentially more reversible with treatment. Other studies 11,12,13 have also suggested that the success of thrombolytic therapy for HVOD depends on early treatment, especially before MOF develops. Bearman et al 12 showed that MOF before the start of thrombolytic therapy was an important adverse prognostic factor and that the need for supplemental oxygen, dialysis or mechanical ventilation before start of treatment were associated with lack of response to rtPA treatment.…”
Section: Discussionmentioning
confidence: 99%
“…While recombinant tissue plasminogen activator (rh-tPA) has been used in many patients, only two series have included substantial numbers of patients. 37,38 We reported that 29% of patients responded and that 24% developed life-threatening hemorrhage. In Scriber's series, 38 most patients began treatment when they were suspected to be developing VOD rather than after established criteria were met.…”
Section: Coagulation Parametersmentioning
confidence: 99%
“…37,38 We reported that 29% of patients responded and that 24% developed life-threatening hemorrhage. In Scriber's series, 38 most patients began treatment when they were suspected to be developing VOD rather than after established criteria were met. Of 24 patients who were treated without having met criteria for VOD, 67% responded.…”
Section: Coagulation Parametersmentioning
confidence: 99%